2021
DOI: 10.1037/dev0001222
|View full text |Cite
|
Sign up to set email alerts
|

Children’s outgroup giving in settings of intergroup conflict: The developmental role of ingroup symbol preference.

Abstract: Understanding when children develop a sense of group boundaries has implications for conflict and its resolution. Integrating social identity development theory and the developmental peace-building model, we investigated whether preferences for ethno-religious ingroup symbols mediate the link from child age to outgroup prosocial giving among 5-to 11-year-old children from both majority and minority backgrounds in three settings of protracted intergroup conflict (N = 713, M = 7.97, SD = 1.52, 52.6% female). Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 69 publications
4
32
0
Order By: Relevance
“…Although the positive relation between children's EC and their prosocial behavior has been supported many times in existing literature (e.g., Diener & Kim, 2004; Garner, 2006; Kanacri et al, 2013), relevant studies have not, to our knowledge, examined whether the race of the target mattered. The present study also extended research that focused on children's prosocial behaviors toward various racial outgroups (e.g., Moran & Taylor, 2022; Sierksma et al, 2018; Taylor et al, 2021) and prosocial disparity between ingroup and outgroup recipients by showing the importance of children's EC and parents' implicit racial attitudes as predictors. Results of this study suggested that the direct positive relation between EC and prosocial behavior may apply only for the “ingroup.” Interestingly, our study demonstrated that for White children's prosocial behavior toward Black children, who are both racial outgroup members and historically marginalized peers who have less power and privilege than White people in the United States, the relation between EC and prosocial behavior depended on parents' implicit racial attitudes toward Black people.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although the positive relation between children's EC and their prosocial behavior has been supported many times in existing literature (e.g., Diener & Kim, 2004; Garner, 2006; Kanacri et al, 2013), relevant studies have not, to our knowledge, examined whether the race of the target mattered. The present study also extended research that focused on children's prosocial behaviors toward various racial outgroups (e.g., Moran & Taylor, 2022; Sierksma et al, 2018; Taylor et al, 2021) and prosocial disparity between ingroup and outgroup recipients by showing the importance of children's EC and parents' implicit racial attitudes as predictors. Results of this study suggested that the direct positive relation between EC and prosocial behavior may apply only for the “ingroup.” Interestingly, our study demonstrated that for White children's prosocial behavior toward Black children, who are both racial outgroup members and historically marginalized peers who have less power and privilege than White people in the United States, the relation between EC and prosocial behavior depended on parents' implicit racial attitudes toward Black people.…”
Section: Discussionsupporting
confidence: 76%
“…We used a forced‐choice chocolate‐sharing task to measure children's costly prosocial behavior toward different targets (see Abramson et al, 2018, for a similar task). Distribution tasks similar to the one used in the current study have been used extensively with various resources (i.e., candy, money, stickers) with children in the same age range for decades (see Fehr et al, 2008; Taylor et al, 2021). Large sized gold‐foiled chocolate coins were used in the study.…”
Section: Methodsmentioning
confidence: 99%
“…However, that awareness does not prevent children from empathising with members of the conflict rival group. Given the importance of empathy (Taylor et al, 2020a), particularly out‐group empathy (O’Driscoll et al, 2021) for children's prosocial behaviour in conflict settings (Moran & Taylor, 2021; Taylor et al, 2021a), this finding has implications for the development peacebuilding model. In addition, the findings suggest that parents do not need to protect their children from knowing about the past (Reidy et al, 2015); they are already aware of how it affects the present.…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative task was adapted and applied to explore the majority group children's awareness of symbols associated with the Traveller and settled communities. The structure of this task was adapted from previous studies exploring children's awareness of different social groups (Taylor et al, 2020 , 2021 ; Tomovska Misoska et al, 2020 ), while the content (Traveller/settled images) was modified to the Irish context. The task comprised 20 pairs of hypothesised ingroup, and outgroup symbols derived from previous qualitative studies (Devine et al, 2008 ; Dupont, 2017 ; see Appendix C).…”
Section: Methodsmentioning
confidence: 99%